2009
DOI: 10.1016/j.otsr.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Iliac bone-block autograft for posterior shoulder instability

Abstract: The iliac posterior shoulder bone-block is effective in managing instances of involuntary posterior shoulder instability. A review of the literature confirmed these satisfactory results in terms of non-recurrence, pain relief and function recovery with this technique; the main difficulties of this technique remains in the correct positioning of the bone-block and the proper orientation of the fixation screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
83
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 14 publications
1
83
1
1
Order By: Relevance
“…Three-dimensional reconstructions with humeral head subtraction can improve the accuracy of quantifying the extent of glenoid bone loss. 1,[4][5][6] It is well recognized that anterior glenoid bone loss is a significant contributor to recurrent anterior instability if the defect amounts to greater than 25% of the articular surface. The current gold-standard treatment for glenoid bone loss in the setting of recurrent instability is a coracoid transfer with the Bristow-Latarjet procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional reconstructions with humeral head subtraction can improve the accuracy of quantifying the extent of glenoid bone loss. 1,[4][5][6] It is well recognized that anterior glenoid bone loss is a significant contributor to recurrent anterior instability if the defect amounts to greater than 25% of the articular surface. The current gold-standard treatment for glenoid bone loss in the setting of recurrent instability is a coracoid transfer with the Bristow-Latarjet procedure.…”
Section: Discussionmentioning
confidence: 99%
“…As such, bone augmentation procedures for posterior glenoid bone loss have been described in a similar fashion to anterior glenoid bone loss to prevent recurrent instability (Table 1). [4][5][6] In this technique article with video, we describe an arthroscopic technique using fresh distal tibial allograft for posterior glenoid augmentation.…”
mentioning
confidence: 99%
“…1,2 Commonly, soft-tissue reconstructions are performed in the case of capsulolabral lesions and normal bony anatomy, but especially in the presence of traumatic posterior bony Bankart lesions, glenoid erosion, or posterior glenoid dysplasia, open bone grafting techniques have been reported [3][4][5][6][7] ( Fig 1, Table 1). Even in the absence of osseous deficiency, many authors have performed posterior bone block procedures to reduce the high rate of recurrent instability reported after soft-tissue repairs.…”
mentioning
confidence: 99%
“…Even in the absence of osseous deficiency, many authors have performed posterior bone block procedures to reduce the high rate of recurrent instability reported after soft-tissue repairs. [3][4][5] In such cases, the bone graft is intended to extend the glenoid surface rather than to act as an anatomic repair. Recently, biomechanical studies have shown reduced posterior and posteroinferior translation of the humeral head after a posterior bone block procedure, and the importance of the posterior Bankart repair was shown regarding the re-establishment of inferior joint stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation